Anaerobic digestion of lignocellulosic waste: Environmental impact and economic assessment. (1st February 2019) - Fan, Yee Van; Klemeš, Jiří Jaromír; Perry, Simon; Lee, Chew Tin
Abstract: Lignocellulosic waste (LW) is abundant in availability and is one of the suitable substrates for anaerobic digestion (AD). However, it is a complex solid substrate matrix that hinders the hydrolysis stage of anaerobic digestion. This study assessed various pre-treatment and post-treatments of lignocellulosic waste for anaerobic digestion benefiting from advanced P-graph and GaBi software (Thinkstep, Germany) from the perspective of cost and environmental performances (global warming potential, human toxicity, ozone depletion potential, particulate matter, photochemical oxidant creation, acidification and eutrophication potential). CaO pre-treatment (P4), H2 S removal with membrane separation post-treatment (HSR MS) and without the composting of digestate is identified as the cost-optimal pathway. The biological (P7- Enzyme, P8- Microbial Consortium) and physical (P1- Grinding, P2- Steam Explosion, P3- Water Vapour) pre-treatments alternatives have lower environmental impacts than chemical pre-treatments (P4- CaO, P5- NaOH, P6- H2 SO4 ) however they are not part of the near cost optimal solutions. For post-treatment, the near cost optimal alternatives are H2 S removal with organic physical scrubbing (HSR OPS) and H2 S removal with amine scrubbing (HSR AS). HSR AS has a better performance in the overall environmental impacts followed by HSR MS and HSR OPS. In general, the suggested cost-optimal solution is still having relatively lower environmental impacts and feasible for implementation (cost effective). There is very complicated to find a universal AD solution. Different scenarios (the type of substrate, the scale, product demand, policies) have different constraints and consequently solutions. The trade-offs between cost and environment performances should be a future extension of this work. Highlights: The pre-and post-treatments of lignocellulosic waste anaerobic digestion are assessed. The assessment is from the perspective of cost and environmental performance. P-graph approach is applied to identify the cost optimal solution. The cost optimal and near cost optimal solutions are considered in evaluating the environmental performance. The feasible solutions are suggested and discussed.